Kajian Teknis Kapasitas Produksi dan Efisiensi Kerja Conveyer Belt Dalam Pengiriman Batubara Menuju Stockpile Di PT. Singlurus Pratama - Faisal Manta; Reza Naufal Hanifudin (Politeknik Negeri Lhokseumawe, 2022)
PT. Singlurus Pratama has a fairly high mining productivity, so a stockpile is needed as a temporary coal storage place. Stockpile owned by PT. Singlurus Pratama has a capacity of 140,000 tons. The crushed coal is carried by a conveyor belt to be transported to the stockpile. Conveyor belt at PT. Singlurus Pratama has different sizes so that the efficiency of each belt for transporting coal varies. In the next planning, an increase in production targets will be carried out, so research is urgently needed on the efficiency value of each type of belt owned. This data is needed to determine the type of belt that is in accordance with the production target so as to provide optimal conveyor belt service life performance. Efficiency calculation begins by measuring the value of the theoretical and actual production capacity of each type of belt to get the value of the production rate index (PRI). PRI is the value of work efficiency based on two load conditions, namely minimum and maximum, then the value of work efficiency for all types of belts at PT. Singlurus Primary is known accurately. In the study, it was found out that the production capacity of conveyor belts in coal delivery to the stockpile for type BC-01, BC-02, BC-03 and Tripper Cars were 1,690, 1,698, 1,742, 2,371 tons/hour, with the lowest value for type BC-01. and the highest value of the Tripper Car type. The minimum load efficiency values for the conveyor belt types BC-01, BC-02, BC-03 and Tripper Car are 22.2, 22%, 22% and 16%, respectively. The maximum load efficiency values for the conveyor belt types BC-01, BC-02, BC-03 and Tripper Car are 37%, 37%, 36% and 26%, respectively. Then the minimum and maximum workload efficiency values are the highest on the BC-01 type and the lowest on the Tripper car type.